PERTUMBUHAN VEGETATIF DUA VARIETAS JAGUN G PADA TANAH GAMBUT YANG DIBERI LIMBAH PULP & PAPER - Ermanita '; Yusnida Bey; Firdaus LN (Program Studi Pendidikan Biologi, 2004)
Vegetative growth performance of two varieties of maize by pulp and paper waste application has been studied in peat soils using Factorial Completely Randomized Design in biological garden, faculty of education and teacher training, Riau University. The experiments were arrange by factorial 2 x 5 and three replications. First factor was two maize varieties i.e. Arjuna and Bisi-2. Second factor was Pulp and Paper waste taken from Riau Pulp and Paper Industry. Rate of application were 0, 15, 20, 25, and 30 gr kg 1peat soils. Plant height, leaf length, leaf wide and plant dry weight were measured. Data analyzed by using ANAVA dan Duncan’s Multiple Range Test at 5% level of signification. The results shows that plant height and leaf length has significance difference between two maize varieties, but not for leaf wide and dry weight. There were no significant interactions effects for all parameters observed. We conclude that the varieties of Arjuna more tolerance and adaptive to peat soil.Key words : pulp and paper industrial waste, maize tolerance, vegetative growth